Exploring the Role of Nutrition and Physiology in Basketball Performance : A Literature Review - Muhamad Ramos; Ronni Yenes; Eri Barlian; Hendri Neldi; Yovhandra Ockta (Postgraduate, University of Mataram, 2024)
Basketball is a high-intensity sport that requires exceptional physical performance, including strength, speed, and endurance. Beyond technical skills, physiological factors such as nutrition play a crucial role in optimizing performance. Articles were sourced from Scopus, PubMed, and Google Scholar, using keywords such as